Testing the middle income trap for upper middle income countries by fourier cointegration - Peker, Ayşe Esra; Çak, Merve Nur (Rating Academy, 2022)
The middle income trap is defined as the inability to rise to a higher income group after the gross domestic product value reaches the middle income level and is stuck in a certain income range. Based on this point, the data used in the study covers the period 1960-2019. The middle income trap hypothesis was tested for upper middle income country groups in 2019 and has been included in the 22 countries included in the study. The per capita Gross Domestic Product data for the mentioned countries and the reference country were obtained from the World Bank database. In the study, in order to perform the Banerjee Arcabic Lee (2017) Fourier ADL cointegration test, the variables used in the analysis should be first-order I (1) stationary. For this reason, before the cointegration test, Ng-Perron Test (2001), Enders and Lee (2012) Fourier Function Stationarity Test, Christopoulos and Leon Ledesma (2010) Fourier CSR Stability tests were performed to determine the stationarity levels of variables. And then the Banerjee Arcabic Lee (2017) Fourier ADL cointegration test was applied to the above mentioned 16 countries. According to the results of Fourier ADL Cointegration, the null hypothesis, which asserts that there is no cointegration for Botswana, Brazil, China, Colombia, Ecuador, Fiji, Gabon, Guatemala, Iran, Jamaica, Malaysia, Peru, South Africa, Suriname, Trinidad and Tobago, including Turkey cannot be rejected within 5% significance level. Therefore, empirical evidence has been obtained that these countries are in the middle income trap.

The middle income trap is defined as the inability to rise to a higher income group after the gross domestic product value reaches the middle income level and is stuck in a certain income range. Based on this point, the data used in the study covers the period 1960-2019. The middle income trap hypothesis was tested for upper middle income country groups in 2019 and has been included in the 22 countries included in the study. The per capita Gross Domestic Product data for the mentioned countries and the reference country were obtained from the World Bank database. In the study, in order to perform the Banerjee Arcabic Lee (2017) Fourier ADL cointegration test, the variables used in the analysis should be first-order I (1) stationary. For this reason, before the cointegration test, Ng-Perron Test (2001), Enders and Lee (2012) Fourier Function Stationarity Test, Christopoulos and Leon Ledesma (2010) Fourier CSR Stability tests were performed to determine the stationarity levels of variables. And then the Banerjee Arcabic Lee (2017) Fourier ADL cointegration test was applied to the above mentioned 16 countries. According to the results of Fourier ADL Cointegration, the null hypothesis, which asserts that there is no cointegration for Botswana, Brazil, China, Colombia, Ecuador, Fiji, Gabon, Guatemala, Iran, Jamaica, Malaysia, Peru, South Africa, Suriname, Trinidad and Tobago, including Turkey cannot be rejected within 5% significance level. Therefore, empirical evidence has been obtained that these countries are in the middle income trap.
Testing the middle income trap for upper middle income countries by fourier cointegration
Keywords: Business Administration; İşletme